Meaningful Memory in Acute Anorexia Nervosa Patients—Comparing Recall, Learning, and Recognition of Semantically Related and Semantically Unrelated Word Stimuli. (29th December 2016) - Terhoeven, Valentin; Kallen, Ursula; Ingenerf, Katrin; Aschenbrenner, Steffen; Weisbrod, Matthias; Herzog, Wolfgang; Brockmeyer, Timo; Friederich, Hans‐Christoph; Nikendei, Christoph
Abstract: Objective: It is unclear whether observed memory impairment in anorexia nervosa (AN) depends on the semantic structure (categorized words) of material to be encoded. We aimed to investigate the processing of semantically related information in AN. Method: Memory performance was assessed in a recall, learning, and recognition test in 27 adult women with AN (19 restricting, 8 binge‐eating/purging subtype; average disease duration: 9.32 years) and 30 healthy controls using an extended version of the Rey Auditory Verbal Learning Test, applying semantically related and unrelated word stimuli. Results: Short‐term memory (immediate recall, learning), regardless of semantics of the words, was significantly worse in AN patients, whereas long‐term memory (delayed recall, recognition) did not differ between AN patients and controls. Discussion: Semantics of stimuli do not have a better effect on memory recall in AN compared to CO. Impaired short‐term versus long‐term memory is discussed in relation to dysfunctional working memory in AN. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.